2015
DOI: 10.1242/jcs.175232
|View full text |Cite
|
Sign up to set email alerts
|

Localized control of oxidized RNA

Abstract: The oxidation of biological molecules by reactive oxygen species (ROS) can render them inactive or toxic. This includes the oxidation of RNA, which appears to underlie the detrimental effects of oxidative stress, aging and certain neurodegenerative diseases. Here, we investigate the management of oxidized RNA in the chloroplast of the green alga Chlamydomonas reinhardtii. Our immunofluorescence microscopy results reveal that oxidized RNA (with 8-hydroxyguanine) is localized in the pyrenoid, a chloroplast micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…5A, Fig. S3), as in lichenized Trebouxia (Candotto Carniel et al, 2015), perhaps related to compartmentalizing oxidized mRNAs in the pyrenoid (Zhan et al, 2015). Fluorescent DCF also accumulated in the periplasmic space in the aquatic, but not the desert, taxa (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…5A, Fig. S3), as in lichenized Trebouxia (Candotto Carniel et al, 2015), perhaps related to compartmentalizing oxidized mRNAs in the pyrenoid (Zhan et al, 2015). Fluorescent DCF also accumulated in the periplasmic space in the aquatic, but not the desert, taxa (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The ΔrbcL mutant carries a disruption of the chloroplast gene encoding RbcL and lacks a pyrenoid [ 24 , 34 ]. Analysis by SDS-PAGE and silver staining revealed that P fractions from ΔrbcL lacked both RbcL and RbcS, which is known to have a very low abundance in RbcL-deficient mutants [ 25 ] ( Fig 1D ). The Rubisco deficiency of ΔrbcL considerably alters cellular metabolism and might therefore alter the non-pyrenoid proteins in the P fraction, thereby biasing the subtraction of contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic conservation of the DLA2 amino acid sequence and RNA binding properties suggests that it performs a similar dual function in seed plants (Bohne et al, 2013). A moonlighting function was also suggested for RbcL, which was shown to bind RNA (Yosef et al, 2004;Cohen et al, 2006) and recently has been proposed to be involved in the redox stress-induced localization of oxidized chloroplast RNAs in Chlamydomonas, independent of its function in the Rubisco complex (Zhan et al, 2015). Moreover, recent in vitro data suggest that PsbD protein synthesis in Chlamydomonas is metabolically controlled (Schwarz et al, 2012;see above).…”
Section: Translational Regulation In Response To Other Internal and Ementioning
confidence: 96%